Lectotypification, synonymy, and a new name in Senna series Aphyllae (Leguminosae: Caesalpinioideae) - Robbiati, Federico Omar (2014)
In series Aphyllae, Senna acanthoclada is lectotypified based on images housed at Albrecht von Haller Institute of Plant Sciences, Universität Göttingen; a new circumscription and synonyms for S. aphylla are given, and a new name: S.aphylla var. pendula var. nov. is proposed.